Aedes aegypti mosquitoes at nonresidential sites might be related to transmission of dengue virus in Monterrey, Northeastern Mexico - Zárate Nahón, Erwy Arvid; Ramírez Jiménez, Rocío; Alvarado Moreno, Marcela Selene; Sánchez Casas, Rosa María; Laguna Aguilar, Maricela; Sánchez Rodríguez, Olga Saraí; Rivas Estilla, Ana María; Ramos Jiménez, Javier; Medina de la Garza, Carlos Eduardo; Villarreal Pérez, Jesús Zacarías; Fernández Salas, Ildefonso (Society of Southwestern Entomologists, 2013)
has been assumed to be households. In Mexico, dengue outbreaks continue year after year despite intense control efforts. Nonresidential sites (public and private spaces) infested with Aedes aegypti (L.) were evaluated. In total, 141 nonresidential sites were sampled for the presence of potential and active oviposition sites and adult mosquitoes. Eighty percent of the sites were oviposition sites; Ae. aegypti adults were recovered at 94.7% of nonresidential sites. Most female Ae. aegypti, 21.6 and 10.4, were at schools and recreational sites, respectively. Chi-squared indicated no significant differences in the dengue vector to categories of sample sites